An Analysis on The Students’ Ability in Comprehending Report Text in Reading at SMA Negeri 1 Siborongborong - Siahaan, Rekolina; Situmorang, Titin Elfrida; Saragih, Mariati (Innovative: Journal Of Social Science Research, 2025)
Talking about the analysis of students' ability to understand the report text in the eleventh grade of SMA Negeri 1 SIBORONGBORONG, where the research problem is “How is the student's ability to understand the report text at the reading level at SMA Negeri 1 Siborongborong?”. The subjects of this study were SMA Negeri 1 Siborongborong grade XI students, there were 8 classes consisting of 288 students and the author took 72 students as samples. From the data analysis, it was obtained that the students' abilities were at a moderate level, where students who obtained scores of more than 85.8 were only 13 students, between 69.41 - 85.8 were 41 students and students with low abilities or obtained scores less than 69.41 were 18 students. From these findings, the author concludes that, grade XI students do not have high abilities, and some of them cannot understand the report text well. As a result, the ability of grade XI students of SMA Negeri 1 Siborongborong is at a moderate level.